Penyuluhan Pentingnya Makanan Sehat Untuk Mewujudkan Keluarga Sehat Bagi Masyarakat Desa Bingkat Kecamatan Pegajahan Kabupaten Serdang Bedagai Sumatera Utara - Enny Fitriani; Nur Asyah; Melati Yulia Kusumastuti; Aar Riana; Aling Wong; Wafa Atika (STIKES Columbia Asia Medan, 2026)
Healthy food plays an important role in maintening family healty an supporting the growth and development of family members, especially children. This study aims to improve community knowledge about the importance of consuming nutritious and balanced food in order to achieve a healthy family. The metod used is a quantitative descriptive study with a survey approach through interviews with the community in Bingkat Village, Pegajahan Districh, Serdang Bedagai Regency. The results show that most people already understand the importance of choosing nutritious and balanced food, although there are still limitatiuns in understanding food additives. The aducational program conducted was able to increase pblic awareness in selecting healthy food, thereby helping to prevent digestive disrders, support children’s growth, end maintain overall family health. In outreach, education about healthy food is essential to improve the quality of family health. It s expected that the community can implement a balanced nutritional diet to achieve a healthy family.